2021
DOI: 10.1016/j.apsb.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetically-engineered “all-in-one” vaccine platform for cancer immunotherapy

Abstract: An essential step for cancer vaccination is to break the immunosuppression and elicit a tumor-specific immunity. A major hurdle against cancer therapeutic vaccination is the insufficient immune stimulation of the cancer vaccines and lack of a safe and efficient adjuvant for human use. We discovered a novel cancer immunostimulant, trichosanthin (TCS), that is a clinically used protein drug in China, and developed a well-adaptable protein-engineering method for making recombinant protein vaccines by fusion of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In our previous work, TCS was applied as a vaccine adjuvant and successfully induced cancer immunization 18 , 19 . But its application as an adjuvant therapy to the mainstay immune checkpoint therapy was not yet revealed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, TCS was applied as a vaccine adjuvant and successfully induced cancer immunization 18 , 19 . But its application as an adjuvant therapy to the mainstay immune checkpoint therapy was not yet revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The bone marrow-derived dendritic cells (BMDCs) were induced from the bone marrow mononuclear cells derived from BALB/c mice using mGM-CSF (20 ng/ml) and mIL-4 (10 ng/ml), as described in a previous report 18 . The loosely attached immature DCs were collected for the subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The penetrating peptide (CPP)-fused recombinant TCS toxin conjugated to lactoferrin (LF) has the potential to penetrate the blood–brain barrier (BBB) [ 146 ]. A cancer vaccination platform based on TCS was also implemented in 2021 [ 147 ], which is a promising tool for cancer immunotherapy. In basic science, studies on the TCS-ribosome complex by Cryo-EM will reveal the detail of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TCS could enhance the sensitivity of tumors to chemotherapeutic drug treatment [ 13 , 16 ]. Recombinant TCS has shown potent anti-tumor effects [ 17 , 18 , 19 ]. It is crucial to investigate the anti-tumor mechanisms and potential applications of TCS.…”
Section: Introductionmentioning
confidence: 99%